J17 HD-DRUM – a novel computerised drumming training for movement and cognitive abilities in people with Huntington's disease – app development and protocol of a randomised controlled feasibility study. (12th September 2022) - Metzler-Baddeley, Claudia; Busse, Monica E; Drew, Cheney JG; Pallmann, Philip; Jones, Derek K; Rosser, Anne E
Abstract : Background: Huntington's Disease (HD) causes cell loss in the basal ganglia (BG) that are important for cognitive and motor functions. Learning novel drumming sequences requires BG abilities of attention, multi-tasking, and the planning and execution of motor sequences, all of which are affected in HD. Previously, we observed that rhythmic Bongo drumming improved attention and motor abilities and strengthened callosal white matter pathways in people with HD. Aims: To assess the feasibility of HD-DRUM, a novel computerised drumming training app that optimises the training difficulty for each user with an automatic stair-case procedure. To obtain estimates of effects of HD-DRUM on cognitive and motor abilities and on white and grey matter microstructure in motor and executive networks of the brain. Methods: We will assess the feasibility (recruitment, retention, acceptability, adherence) of three months of HD-DRUM (15 min per day, 5 days a week) in 50 people with HD at premanifest to mild-moderate manifest stages recruited from five clinics in the UK. They will be randomly allocated to the training or a standard-care control group. Further, 25 healthy control participants will be recruited who will also use HD-DRUM. All participants will undergo cognitive and motor assessment (ENROLL protocol) and magnetic resonance imaging of the brain with diffusion-weighted and quantitative magnetization transfer imaging at the beginning and the end of the study. Anticipated Outcomes: If feasible, HD-DRUM may provide a remotely accessible training tool to help improve motor and cognitive symptoms in HD without the risk of harmful side-effects in the future.